High export via small particles before the onset of the North Atlantic spring bloom. Issue 9 (22nd September 2016) - Giering, S. L. C.; Sanders, R.; Martin, A. P.; Lindemann, C.; Möller, K. O.; Daniels, C. J.; Mayor, D. J.; St. John, M. A.
Abstract: Sinking organic matter in the North Atlantic Ocean transfers 1–3 Gt carbon yr −1 from the surface ocean to the interior. The majority of this exported material is thought to be in form of large, rapidly sinking particles that aggregate during or after the spring phytoplankton bloom. However, recent work has suggested that intermittent water column stratification resulting in the termination of deep convection can isolate phytoplankton from the euphotic zone, leading to export of small particles. We present depth profiles of large (>0.1 mm equivalent spherical diameter, ESD) and small (<0.1 mm ESD) sinking particle concentrations and fluxes prior to the spring bloom at two contrasting sites in the North Atlantic (61.30°N, 11.00°W and 62.50°N, 02.30°W) derived from the Marine Snow Catcher and the Video Plankton Recorder. The downward flux of organic carbon via small particles ranged from 23 to 186 mg C m −2 d −1, often constituting the bulk of the total particulate organic carbon flux. We propose that these rates were driven by two different mechanisms. In the Norwegian Basin, small sinking particles likely reached the upper mesopelagic by disaggregation of larger, faster sinking particles. In the Iceland Basin, a storm deepened the mixed layer to >300 m depth, leading to deep mixing of particles as deep as 600 m. Subsequent restratification could trap these particles at depth and lead to high particle fluxes at depth without the need for aggregation ("mixed‐layer pump"). Overall, we suggest that prebloom fluxes to the mesopelagic are significant, and the role of small sinking particles requires careful consideration. Key Points: Vertical depth profiles of sinking particles were collected before the spring bloom Prebloom fluxes by small particles (<0.1 mm) were similar to bloom and postbloom export rates Small particles were likely exported by two mechanisms: aggregation/disaggregation and deep mixing